Validity of 20-MST for predicting VO2max of adult Singaporean athletes. Issue 3 (September 1993) - Sproule, J; Kunalan, C; McNeill, M; Wright, H
Abstract : This investigation compared the results of direct and indirect measurements of maximum oxygen uptake (VO2max) of an Asian population. Twenty subjects (16 male, 4 female), all of whom were physical education students, were assessed directly using laboratory treadmill running to determine VO2max. The indirect estimation of VO2max was obtained using a modified form of the Leger and Lambert 20-m multistage shuttle run test (20-MST). Heart rates were recorded throughout both tests. Pearson product moment correlations confirmed test-retest reliability for both direct and indirect measurements (r = 0.90 and r = 0.91 respectively). Differences for test-retest were found to be not significant. No differences were found between the maximal heart rate responses of the subjects for the direct and indirect tests. Of the subjects 75% had a lower predicted VO2max value (P < 0.01) compared with results gained by direct measurements when the Ramsbottom norms for the 20-MST were used. The reasons for this difference could be due to the different racial groups used as subjects, the climatic conditions in Singapore, or the small sample size. In order for the 20-MST test to be considered a valid measure of aerobic fitness in Singapore with an Asian population further study is recommended.